Unaccusative Verbs in Romance Languages - Mackenzie, I. author. aut Link
XII, 230 p.
Keywords: The author questions the status quo in Romance linguistics. The Ergative/Unaccusative syntactic approach has been accepted as the orthodox analytical paradigm. He re-examines both the theoretical imperative and the empirical evidence for that approach, drawing on a large amount of new and surprising data from Italian, Spanish, French and Catalan.